Usulan Perbaikan Layout Warehouse Dengan Metode Dedicated Storage Pada UD H. Nasir - Muhammad Dhomiri; Deny Andesta (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
This activity aims to find out the management of the warehouse layout for partners. The warehouse has an important role for business actors, if it is used properly, the activities that occur in the warehouse can run smoothly so that it does not cause problems. UD. H Nasir is a business engaged in the sale of shrimp, the problem that occurs in partner storage warehouses is that they do not have arrangements regarding the layout of goods so that goods are not arranged neatly and the material handling process becomes inefficient. To adjust the storage position of goods in the warehouse, a dedicated storage method is used with the calculation of space requirements, throughput, and throughput ranking.